The Role of Operational Analytics in Optimizing Small-Sized Businesses (Global Journal of Management and Business Research, 2025)
Operational analytics has become a transformative tool for small-sized businesses aiming to enhance operational efficiency profitability and scalability This paper explores how small businesses often constrained by limited resources can leverage affordable analytics tools to optimize their operations Through a case study of a small auto-parts dealer this research investigates the practical applications of tools like Google Analytics Zoho Analytics QuickBooks Power BI Tally Prime and Excel The paper identifies key operational areas such as inventory management sales forecasting profitability tracking and customer relationship management The findings demonstrate how these tools contribute to significant improvements in operational efficiency profitability and decision-making processes Ultimately operational analytics proves to be a game-changer for small enterprises driving their competitiveness in a data-driven business environment
Keywords: operations management; small business; data – driven decision; operational analytics; profitability; customer relationship; inventory management